Penerapan Penyelesaian Perkara Melalui Pendekatan Restorative Justice Dalam Penanganan Tindak Pidana Penganiayaan - Rachmat Aribowo; Alvi Syahrin; Sunarmi Sunarmi; Marlina Marlina (USU LAW JOURNAL, 2019)
Abstract. The community is a portrait of life full of disputes, disputes, quarrels, feuds, or various types of conflicts between individuals, groups, families, ethnicities, even between nations that result in various forms of criminal offense including criminal acts both light and heavy as intended Article 351 sd Article 355 of the Criminal Code. For example, dangdut singer Murya Agung aka Dewi Persik, was found guilty of committing a minor offense against Julia Perez as charged with Article 351 paragraph (1) of the Criminal Code. In essence, the court ruling imposed the defendant Dewi Persik for 3 (three) months imprisonment and ordered the defendant to be detained. Apparently opponent play Dewi Persik, Julia Perez punished with the same punishment that is sentenced to prison for 3 (three) months in prison. From the above description, it is appropriate that the concept of restorative justice approach as an alternative to the settlement of criminal offenses is immediately applied in Indonesia as an effort to reform the law. This is because restorative justice is an approach that is more focused on the conditions of creating justice and balance between perpetrators of crime with the victim. The criminal justice-focused criminal justice mechanism and procedure is transformed into a process of dialogue and mediation to create an agreement on the settlement of a fairer and more balanced criminal case for both victims and perpetrators. Restorative justice has a meaning of restoring justice. In the criminal justice is currently known as restitution or compensation for victims, while restoration has a broader meaning. In this study tried to show that the criminal act of persecuting each other is equally harmful to the parties who litigation.   Keywords : settlement of cases; restorative justice; and criminal act of persecution.